2018
DOI: 10.1007/s10120-018-0813-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of targeted therapy with or without chemotherapy in advanced gastric cancer treatment: a network meta-analysis of well-designed randomized controlled trials

Abstract: Apatinib, regorafenib, and rilotumumab improved patient PFS and OS. When combined with chemotherapy, ramucirumab and rilotumumab had high efficacy but low tolerability, and bevacizumab had moderate efficacy and tolerability for PFS. Without chemotherapy, ramucirumab and regorafenib had relatively high therapeutic efficacy tolerability for PFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 35 publications
(56 reference statements)
1
59
2
Order By: Relevance
“…Recently, a network meta-analysis evaluated the efficacy and safety of targeted drugs (mainly including apatinib, regorafenib, rilotumumab, everolimus, bevacizumab, and sunitinib) with or without chemotherapy in advanced GC treatment and demonstrated that apatinib showed the best improvement in PFS, OS, and overall response rate. 43 …”
Section: The Clinical Research Regarding Apatinibmentioning
confidence: 99%
“…Recently, a network meta-analysis evaluated the efficacy and safety of targeted drugs (mainly including apatinib, regorafenib, rilotumumab, everolimus, bevacizumab, and sunitinib) with or without chemotherapy in advanced GC treatment and demonstrated that apatinib showed the best improvement in PFS, OS, and overall response rate. 43 …”
Section: The Clinical Research Regarding Apatinibmentioning
confidence: 99%
“…Gastric cancer (GC) is a severe malignant tumour associated with high mortality, especially in Asia 1,2 . Due to the non-specific symptoms in early appearance and the poor prognosis, the 5-year relative survival rate for GC was at most 20% 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were published for these cancer treatments approved by the U.S. Food and Drug Administration [ 7 ]. It has repeatedly been reported that survival benefit of targeted therapy may come at the cost of toxicity potentiation when provided alone [ 8 ] or in combination with standard or chemotherapy [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. A plethora of studies have been published documenting, besides good clinical outcome, potentiation of toxicities in combination treatment of chemotherapy or standard therapy with mAbs, targeted treatment, or immunotherapy [ 9 , 10 , 11 , 18 ].…”
Section: Introductionmentioning
confidence: 99%